Comparison of movement related cortical potential in healthy people and amyotrophic lateral sclerosis patients - Gu, Ying; Farina, Dario; Murguialday, Ander Ramos; Dremstrup, Kim; Birbaumer, Niels (Frontiers in Neuroscience, 2013)
Objective: To understand the brain motor functions and neurophysiological changes due to motor disorder by comparing electroencephalographic data between healthy people and amyotrophic lateral sclerosis (ALS) patients. Methods: The movement related cortical potential (MRCP) was recorded from seven healthy subjects and four ALS patients. They were asked to imagine right wrist extension at two speeds (fast and slow). The peak negativity (PN) and rebound rate (RR) were extracted from MRCP for comparison. Results: The statistical analysis has showed that there was no significant difference in PN between the healthy and the ALS subjects. However, the healthy subjects presented faster RR than ALS during both fast and slow movement imagination. Conclusions: The weaker RR of ALS patients might reflect the impairment of motor output pathways or the degree of motor degeneration. Significance: The comparison between healthy people and ALS patients provides a way to explain the movement disorder through brain electrical signal. In addition, the characteristics of MRCP could be used to monitor and guide brain plasticity in patients.